Impact of Emotional Intelligence on Leadership Effectiveness in Corporate Settings in South Africa - Carter, Abigail (International Journal of Psychology, 2024)
Purpose: The aim of the study was to analyze the impact of emotional intelligence on leadership effectiveness in corporate settings. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Emotional intelligence (EI) significantly impacts leadership effectiveness in corporate settings. Leaders with higher EI are better able to manage their own emotions and understand others' emotional states, which enhances their decision-making, communication, and conflict resolution skills. These EI competencies foster stronger team cohesion, improved employee morale, and higher overall productivity. In South African companies, leaders with high EI are also better equipped to navigate the challenges posed by organizational changes and cultural diversity, leading to a more positive and resilient work environment. Unique Contribution to Theory, Practice and Policy: Emotional intelligence theory, transformational leadership theory & social and emotional learning may be used to anchor future studies on the impact of emotional intelligence on leadership effectiveness in corporate settings. Organizations can also foster a culture that values emotional intelligence by providing coaching and mentorship programs that emphasize emotional awareness and empathy. Companies can create policies that promote the integration of EI into organizational performance reviews, aligning EI competencies with leadership success criteria.